Impact of an Enhanced Recovery Program for Cesarean Delivery on Postoperative Opioid Use. Issue 2 (24th June 2021) - Lester, S.A.; Kim, B.; Tubinis, M.D.; Morgan, C.J.; Powella, M.F.
Abstract : ( Int J Obstet Anesthesia . 2020;43:47–55) Enhanced recovery programs have been increasingly used following cesarean delivery (CD). In other settings, enhanced recovery after surgery programs have been shown to speed recovery and decrease the postoperative use of opioids. This study aimed to determine whether postoperative opioid consumption would be reduced in CD patients receiving an enhanced recovery program.